Business Ethics: Analysis of al-Ghazali's Economic Thought With Sufism Approach - Ahmad Maulidizen (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
Business is a sector that is practiced by everyone, one reason why many people who are struggling in this sector is driven by their desire to live in prosperity. There is a lot of understanding out there that says that business ethics don't have to be involved, because it will hinder income be earned. This research is a research library with descriptive approaches, which are describing the analysis of Business Ethics: Analysis Of Al- Ghazali's Economic Thought With Sufism Approach. The method of collecting data in this study is documentation, journals and books. Then analyzed using content analysis, which is by analyzing the library data that is descriptive or scientific analysis of the message premise. Data analysis methods are deductive, inductive and comparative. understanding of Al-Ghazali (450-505) regarding the function of ethics in business. According to him, ethics is very important to be included in business activities. We find many ideas like this in some of the phenomenal works, especially in the book Ihya Ulum al-Din. In that case the writer tries to trace some works related to his thoughts, with great hope that he will get the whole idea about ethics in business.